Die Etablierung von Townships mit Streifenparzellen in Kanada (Ontario and Québec).: Landpolitik und Landvermessung in Britisch-Nordamerika 1763-1794 - Eberle, Ingo (ERDKUNDE, 1991)
After the conquest of New France, Great Britain established its own policies for land surveying and land distribution within the new colonies, documented by the numerous instructions directed to the governors of Canada (between 1763 and 1791). The newly developed townships were neither an heritage of the seigneurial long lot system of former New France nor an adaptation to the existing township subdivisions in the neighbouring New England colonies or to the rectangular land survey in the later USA. It was rather a well reflected method that considered the necessity of water-orientated and thereby linear settlement combined with compact property units as well as low costs and simplicity for land surveying. The first instructions oft 7 63 already contained a conception of future land units’ and parcels’ shape. Those ideas had been refined till the early nineties of the 18th century. The result was the establishment of several township models which had been employed in Upper and Lower Canada. The main elements were - large dimension of townships (approximately 100 square miles), - rectangular shape of townships, - a subdivision into several concessions (rows of parcels as survey and property units), - compact strip parcels with a shape of breadth to length in the ratio of one to approximately 2.5 to three and a size of 200 acres. This township scheme has been varied in several times in Ontario, where rectangular land survey has also been applicated during the second half of the nineteenth century. In Quebec it had never been changed. Only the size and shape of the single parcel unit had been changed by subdividing longitudinally after 1840 in order to get smaller land units which approached the shape of former long lots of New France. As a result the whole eastern part of Canada has been mainly surveyed into strip parcel patterns, forming a contrast to the western Canadian square parcel patterns.